الأزمة المالية العالمية وتغير المواقف حول دور الدولة_ تقديم الاقتصاد الإسلامي أنموذجا _ - دوفي, أ. قرمية (Recherches économiques et managériales, 2016)
يشهد الاقتصاد العالمي اضطرابات واختلالات لم يشهدها منذ الكساد العالمي الكبير،ولعلاج هذه الاضطرابات اتخذت العديد من الإجراءات وبذلت العديد من الجهود،ومعظم هذه الإجراءات فيها خروج عن الفكر الرأسمالي وفلسفته في عدم التدخل بشؤون القطاع الخاص، وقد تبلور هذا التدخل من خلال خطة الإنقاذ الأمريكية البالغة 700 مليار دولار لتعبر عن أكبر تدخل حكومي عرفه التاريخ، وهذا ما يؤكد الحاجة إلى دور الدولة لإصلاح ما أفسدته آليات السوق، فالاقتصاد العالمي أصبح يبحث عن بدائل ونماذج مغايرة للخروج من أزمته، لذلك فالفرصة مهيأة الآن لتقديم الاقتصاد الإسلامي أنموذجا للتخفيف من حدة اضطرابات الأسواق العالمية.   Summary   The global economy is witnessing disorders and dysfunctions not seen since the Great Depression, To treat these disorders several measures have been taken and numerous efforts have been made, In most of these procedures there was a departure from the capitalist ideology and philosophy of non-interference in the affairs of the private sector, this kind of governmental interference is explicit by shown in the American rescue plan of 700 Billion Dollar such a governmental interference is considered the biggest interference history has ever known, this underscores the need to reform the role of the state in reforming the market mechanisms, The global economy has benne looking for alternatives and models to come out of its crisis, thus there is now great opportunity ho present the Islamic model of economics to alleviate disorders of the global markets.